(untitled) (Polis (Santiago), 2020)
The following article is presented by the perspective of Human Scale Development and the Paulo Freire’s pedagogical approach. The aim is to connect the fundamental human needs satisfaction on the generation of growing levels of self-reliance, based on the ways such as the transmission of arts, trades and situated knowledge. The methodology used is the study of a comparative case between the communities that belong to the program of Turismo de Base Comunitaria Trawun in Panguipulli, in the South of Chile and the community São Gonçalo Beira Rio in Cuiabá, Mato Grosso, Brasil. As a result of this research, it was identified main challenges and existing potentials in the territory to protect, integrate, and live their own ways of transmitting their knowledge. Hence, it is concluded that education will be more synergetic only to the extent that communities can participate and lead in the development on their own educational process.